Linguistic Feelings of Some English-Speaking Students from the ENS of Maroua (Cameroon) and Strategies for Improving FLE/FLS Skills (London Journal of Research In Humanities and Social Sciences, 2024)
This article analyzes the linguistic feelings of English-speaking students at the ENS de Maroua, regional capital of the Far North. The twenty respondents come from the Regions of North-West and South-West in Cameroon. English, their language of schooling in primary school and secondary education is now a minority alongside vehicular and local languages in thetown of Maroua. The survey presents a diversity of situations and illustrates a variation of relations to French. The study experiments with the linguistic imagination protocol developed by A-M. Houdebine (2002). The results present representative perceptions of desire, derision, repression as well as linguistic failures. Some respondents want to improve their levels but others are demotivated by a language policy promoting vernacular languages. Facilitating strategies are also proposed for improving FLE/FLS skills. Although In transfer and reception linguistic-cultural values and standards are not always equitable between Regions English speakers and the French speaking part of a country where French-English bilingualism is nevertheless official.
Keywords: Modeling.; techniques; javelin throwing; individualization; ideology; Violence; Values; axiology; drama; manipulation; totalitarianism; superman; Mother child relations. Parent child relations. Premature birth.